2014
DOI: 10.1310/hpj4901-52
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Carboxymaltose

Abstract: Each month, subscribers to The Formulary Monograph Service receive 5 to 6 well-documented monographs on drugs that are newly released or are in late phase 3 trials. The monographs are targeted to Pharmacy & Therapeutics Committees. Subscribers also receive monthly 1-page summary monographs on agents that are useful for agendas and pharmacy/nursing in-services. A comprehensive target drug utilization evaluation/medication use evaluation (DUE/MUE) is also provided each month. With a subscription, the monographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although listed in the drug label as a potential side effect, the overall incidence and the clinical relevance of this adverse event are largely unknown. 11,60,61 This systematic review and meta-analysis show that the reported incidence of hypophosphataemia after infusion of FCM or IIM ranges from 0% to 92% of in prospective clinical trials. Our systematic review and meta-analysis show that this wide range is in part attributable to inconsistent assessment and reporting of hypophosphataemia in clinical studies.…”
Section: Resultsmentioning
confidence: 97%
“…Although listed in the drug label as a potential side effect, the overall incidence and the clinical relevance of this adverse event are largely unknown. 11,60,61 This systematic review and meta-analysis show that the reported incidence of hypophosphataemia after infusion of FCM or IIM ranges from 0% to 92% of in prospective clinical trials. Our systematic review and meta-analysis show that this wide range is in part attributable to inconsistent assessment and reporting of hypophosphataemia in clinical studies.…”
Section: Resultsmentioning
confidence: 97%
“…In terms of efficacy, our study was similar to prospective studies showing a rapid elevation in hemoglobin and ferritin levels [ 36 , 37 ]. Regarding side effects, in clinical trials, serious anaphylactic/anaphylactoid reactions have been reported in 0.1% of patients treated with FCM [ 38 ]. Other serious reactions potentially related to hypersensitivity, including pruritus, rash, urticaria, wheezing, or hypotension, were experienced by 1.5% of cases versus 3.8% of patients with hypertension [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other serious reactions potentially related to hypersensitivity, including pruritus, rash, urticaria, wheezing, or hypotension, were experienced by 1.5% of cases versus 3.8% of patients with hypertension [ 39 ]. Hypophosphatemia is not systematically assessed in clinical trials but when done its rate is about 2.1% [ 38 ], while other studies have reported higher rates. In the study assessing the effect of a single dose of FCM in fatigued women, Favrat et al [ 28 ] have indeed found that 86% of patients had a phosphate level <0.8 mmol/L at day 7 which resolved spontaneously before the end of the study in almost all FCM-treated patients; however, no data on the risk of profound hypophosphatemia (<0.32 mmol/L), fatigue persistence, and hypophosphatemia development were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) guideline recommends IV iron formulations [such as ferric carboxymaltose (FCM)] that allow a high-dose low-frequency strategy for ND-CKD patients [ 8 ]. FCM is a stable, non-dextran iron formulation providing a rapid and efficient repletion of iron stores [ 9 , 10 ] with a controlled delivery of high iron doses into target tissues. In addition, the European Society of Cardiology guideline goes beyond the nephrologist perspective and recommends the use of FCM in patients with heart failure with reduced ejection fraction and iron deficiency with or without anaemia [ 11 ], given the positive results observed in randomized clinical trials [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%